Multiobjective optimization method based on a genetic algorithm for switched reluctance motor design - Mirzaeian, B.; Moallem, M.; Tahani, V.; Lucas, C. (IEEE transactions on magnetics, 2002)
In this paper, a novel multiobjective optimization method based on a genetic-fuzzy algorithm (GFA) is proposed. The new GFA method is used for optimal design of a switched reluctance motor (SRM) with two objective functions: high efficiency and low torque ripple. The results of the optimal design for an 8/6, four-phase, 4 kW, 250 V, 1500 r.p.m. SRM show improvement in both efficiency and torque ripple of the motor.